Higher Rate of Postoperative Complications in Delayed Achilles Tendon Repair Compared to Early Achilles Tendon Repair: A Meta-Analysis - Shu-Kun He; Jing-Ping Liao; Fu-Guo Huang (Journal of Investigative Surgery, 2022)
Background Some authors found that delayed repair of Achilles tendon ruptures achieved similar functional outcomes when compared with acute repair of Achilles tendon ruptures. The purpose of our study was to compare functional outcomes and complication rates of acute repair to delayed repair after Achilles tendon ruptures. Methods PubMed, Embase (Ovid) and the Cochrane Library were searched. Results For Achilles tendon rupture score (ATRS), the overall result revealed that there was no significant difference in ATRS between acute repair groups and delayed repair groups (P = 0.59). For Tegner scores, Halasi scores and Achilles tendon resting angle (ATRA), there was no significant difference between the two groups (P = 0.28, P = 0.47 and P = 0.68). There was no significant difference in the subjective assessment between acute repair groups and delayed repair groups (P = 0.84). However, delayed repair groups showed a higher incidence of complications than acute repair groups (P = 0.01). Subgroup analyses showed that the mean time from injury to surgery of delayed repair groups affect the pooled result substantially. For mean time less than 28d, there was no difference in the incidence of complications between acute repair groups and delayed repair groups (P = 0.09). However, for mean time more than 28d, delayed repair groups showed a higher incidence of complications than acute repair groups (P = 0.05). Conclusion Our study showed delayed repair could obtain similar functional outcomes and subjective assessment when compared with acute repair. However, the rate of complications after delayed repair was higher than that of early repair. Further high-quality randomized controlled trials (RCT) are needed to evaluate the difference.